O regionalizmach tytka i tyta - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
Regional words tytka and tyta persist among the lexical separateness in several regions of Poland. The noun tytka is often used in the traditional meaning ‘the paper bag’, but also in the extended scope ‘the packaging of other material’. The stabilization of both lexemes in regional varieties of Polish is reinforced by well-known customs (Silesian tyta /tytka for first graders) as well as new social campaigns such as “Charity tytka”.